(untitled) (Malaysian Management Journal, 1999)
This study uses monthly return data on 213 stocks listed on the main board of Kuala Lumpur Stock Exchange, Malaysia for the period September 1988 to June 1997 to compare two frequently cited asset pricing models: the capital asset pricing model, CAPM and the arbitrage pricing theory, APT. A comparison was performed along the lines of Chen (1983) and the results showed the APT to perform better than the CAP/ in explaining the variations in cross section of returns. The implication for investors is that the market index is but one of several sources of risk, which should be taken into account in any decision governing investment in the stock market.